THE RELATIONSHIP BETWEEN SOCIO-POLITICAL DIALOGUE AND SOCIOLOGICAL DISCOURSE IN THE PROCESS OF SOCIO-POLITICAL CHANGES IN UZBEKISTAN - Siyaeva Gulnora Ashrafovna (American Journals, 2024)
This article analyzes the role of sociological discourse in the development of the socio-political and socio-cultural life of the country and its conceptual scientific and methodological foundations. The role and importance of sociological discourse in achieving a high level of political consciousness and worldview of citizens is enormous. The development of civil initiatives and their role in building a dialogue between the government and civil society are also considered.
Keywords: socio-political consciousness, socio-political communication, sociological discourse, social development, state, civil society, public initiative.